Evaluation of Pain Tolerance Based on a Biomechanical Method for Human-Robot Coexistence - SUITA, Kazutsugu; YAMADA, Yoji; NAKAMURA, Hisanori; SUGIMOTO, Noboru; MIURA, Hironori; IKEDA, Hiroyasu (Nihon Kikai Gakkai ronbunshū. C, 1997)
In this paper, we discuss human pain tolerance for the design standard of a human-robot coexistence system. Among human sensations, somatic pain is like an emergency call. It is regarded as a stable sensation having neither individual variations nor adaptations. Therefore, we adopt somatic pain which can tolerate repeated mechanical stimuli. We carry out experiments to measure the threshold of human pain tolerance using a biomechanical method and statistical analysis. Moreover, we clarify human pain tolerance when a static or dynamic stimulus is applied. Human pain tolerance is characterized uniformly in terms of the pain intensity curve (PIC) which is fitted to the minimum values of both the static and the dynamic pain tolerance. Moreover, we investigated the relationship between the deformation and velocity of the human sections of our interest, when the human subjects felt somatic pain. Human pain tolerance will be a trigger to build up an advanced safety design standard.